Exchange rate analysis USDMXN, GBPMXN, EURMXN using RSI and Stochastic Oscillators during the COVID19 pandemic - Mata Hernández, José Miguel (Universidad de Sonora, 2021)
The use of technical analysis tools such as the relative strength index (Wilder, 1978) and stochastic oscillators in their versions of fast and slow (Lane, 1984), can serve the investor for better decision making to make investment operations. COVID19 had an impact on the financial markets, a market that was badly affected, was the foreign exchange market, where the exchange rates of the Mexican peso presented a fluctuation and volatility due to the effects of the pandemic as for other issues during 2020. The use of these indicators allowed to visualize the movements that made the currency pairs of USDMXN, EURMXN and GBPMXN during the pandemic and how with the use of these tools, decisions could have been made.